Brain volumetric changes in patients with spinocerebellar ataxia type-2 (Annals of Medical Research, 2024)
Aim: Spinocerebellar ataxia type 2 (SCA2) is a trinucleotide repeat disorder characterized by mutations in the ataxin-2 gene. Although the primary symptoms of this disease are related to cerebellar involvement, such as ataxia and dysarthria, cognitive disorders associated with supratentorial involvement, depression, and extrapyramidal symptoms are also common. The aim of this study was to investigate volumetric changes in patients with SCA2.Materials and Methods: Nine SCA2 patients and sixteen age and gender-matched healthy controls were included in the study. Voxel-based morphometry (VBM) was used to explore changes in whole brain gray and white matter, while surface-based morphometry (SBM) was employed to investigate changes in cortical thickness (CT), local gyrification index (LGI), sulcal depth (SD), and fractal dimension (FD). Deep learning methods were utilized for the automatic segmentation of subcortical gray matter structures and extrapyramidal system structures. Comparisons between groups were made using GLM, T-Test, and Mann-Whitney U test.Results: VBM results showed widespread gray matter loss in the cerebellum and widespread white matter loss in the brain stem (Cluster size: 25918 voxels for gray matter, 24557 voxels for white matter). SBM findings indicated a decrease in cortical thickness (Cluster size:19276 vertices for left hemisphere; 17276 vertices for right hemisphere), more pronounced in the supratentorial frontoparietal region, while FD, LGI, and SD did not differ between groups. Volume loss was observed in the subthalamic nucleus, globus pallidus internus and externus, and red nucleus in SCA2 patients.Conclusion: SCA2 patients exhibit white and gray matter volume loss in the infratentorial region. Additionally, they show a decrease in frontoparietal cortical thickness, while FD, LGI, and SD do not show any changes. Moreover, atrophy is also observed in the extrapyramidal system structures.
Keywords: SCA2; Voxel-based morphometry; Surface-based morphometry; Cortical thickness; Subthalamic nucleus